Geological and Geophysical Studies of the Charlie Gibbs Fracture Zone (North Atlantic) - Skolotnev S. G.; Sanfilippo A.; Peyve A. A.; Nestola Y.; Sokolov S. Y.; Petracchini L.; Dobrolybova K. O.; Basch V.; Pertsev A. N.; Ferrando C.; Ivanenko A. N.; Sani C.; et al. (Doklady Earth Sciences, 2021)
Abstract: The geological and geophysical data obtained during the 50th cruise of R/VAkademik Nikolaj Strakhovon the Charlie Gibbs megatransform system structure in the North Atlantic are presented. The structure of the Charlie Gibbs Fracture Zone was examined in detail, considering previously published data. It has been shown that the northern and southern segments of the Mid-Atlantic Ridge, separated by the Charlie Gibbs transform fault, are entirely different in morphology, and hence in terms of formation. The dredged rocks are represented by an entire spectrum from the mantle to upper crustal varieties and allow us to determine the origin of the main structures of the Charlie Gibbs megatransform system considering detailed data on the morphology.